Insects as feed: Gendered knowledge attitudes and practices among poultry and Pond Fish farmers in Kenya - Waithanji, E.; Affognon, Hippolyte D.; King’ori, S.; Diiro, G.; Nakimbugwe, D.; Fiaboe, K.K. (Informa UK Limited, 2020)
This qualitative study on knowledge, attitudes and practices (KAP) among poultry and pond fish farmers from Kisii, Nakuru and Kirinyaga counties in Kenya was conducted to establish insect for feed interventions likely to reduce the cost of feeds in these enterprises and benefit women and men equitably. Data were collected through sex and enterprise type disaggregated focus group discussions with farmers.